Kesan gaya berfikir dan kemahiran penyelesaian masalah inventif terhadap kemahiran penyelesaian masalah - Sai’en, Shanty (2020)
The Critical and Creative Thinking Skills Model (CCTS) aims to adopt critical and creative thinking skills among students in order to solve problems effectively. However, the majority of teachers have overlooked the importance of this thinking style because of focusing on problem-solving. Therefore, the teaching module based on Meyer’s Model has developed to assist the teachers in teaching problem-solving skills. This module was developed with a combination of critical and creative thinking styles, based on the Inventive Problem-Solving Theory (TRIZ). This theory using a structured and systematic method to solve inventive problems. The purpose of this study is to assess the effect of the Critical Creative Thinking Skills Model implementation on Inventive Problem-solving Skills achievement among students in standard four (design and technology), which involved five aspects namely situational problems, sources of problems, strategies and approaches, flexibility, and originality/innovation. Quasi-experimental research design was used which involved pre-test and post-test. 106 students were selected based on clustered random sampling techniques and divided into a control group (52 students) and a treatment group (54 students). The instruments used in this study involved pre-test, and post-test to assess the Inventive Problem-solving Skills achievement. The outcome of the MANCOVA analysis indicates a significant improvement in all five aspects of student’s Inventive Problem-solving Skills. In sum, thinking style and Inventive Problem-solving Skills Module based on the Inventive Problem-solving Theory may assist teacher’s learning and teaching process in the classroom, especially the creation of ideas to solve problems. Exposures to the critical and creative thinking style indirectly may produce balanced individuals that potentially solve problems efficiently.